2013
DOI: 10.1177/0956462412472317
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous clearance and treatment of acute hepatitis C infection in HIV-positive men with 48 weeks of interferon-alpha and Ribavirin

Abstract: Acute hepatitis C infection in the context of HIV is an emerging problem in men who have sex with men (MSM). We conducted a retrospective cohort study of MSM diagnosed with and treated for acute hepatitis C infection over 10 years. Genotype 1 was the commonest type representing 69% of cases; the spontaneous clearance rate was 20%. The overall sustained virological response (SVR) rate on an intention-to-treat basis was 83%; SVR and was 92% for those completing 48 weeks of treatment. The presence of detectable R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Of the 8 studies with ITT analysis [6,38,39,40,43,46,47,48], 189 of 258 patients achieved an SVR (73.2%; 95% CI 64.2-80.5). Four [41,42,44,45 ]studies without ITT analysis reported treatment success in 134 of 192 patients (68.9%; 95% CI 56.7-78.9) [41,42,44,45].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 8 studies with ITT analysis [6,38,39,40,43,46,47,48], 189 of 258 patients achieved an SVR (73.2%; 95% CI 64.2-80.5). Four [41,42,44,45 ]studies without ITT analysis reported treatment success in 134 of 192 patients (68.9%; 95% CI 56.7-78.9) [41,42,44,45].…”
Section: Resultsmentioning
confidence: 99%
“…Eight were prospective in study design [6,38,39,41,44,45,47,48]. Most studies [6,38,39,40,43,46,47,48] featured an ITT analysis. One study [46] included 3 patients who were each treated twice for 2 separate a-HCV infections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations